(untitled) (Gilgameš, 2016)
The Arab tribe of the Banū Ghassān, ruled by the Jafnid dynasty, emigrated in the Late Antiquity from the Southern Arabian Peninsula to the Balqā’ region in the Levant, near the limes arabicus. Later, the Byzantine emperors appointed the Jafnids with an official recognition (foedus) which gave them a great political and military role in the territories subject to them. The lands of the Ghassanids acted indeed as a buffer zone against the Sasanian Empire. After the Christianization of the tribe, the Jafnids began a process of emulation and cultural assimilation to the Byzantine identity. Finally, the development of the Jafnids’ society was abruptly interrupted by the dissolution of their alliance with the Byzantines at the end of Jāhiliyya, when the brief power of the foederati was replaced by the more lasting domination of the new Islamic Empire. This paper focuses on one of the recent issues brought to scholarly attention: the research of the archaeological evidence connected with the Jafnids. The study, through some epigraphic, iconographic and archaeological sources, examines the Arab elites as both rulers and benefactors with the patronage of several churches, monasteries and other buildings.